SOLES. VII. The Spin–Orbit Alignment of WASP-106 b, a Warm Jupiter along the Kraft Break - Josette Wright; Malena Rice; Xian-Yu Wang; Kyle Hixenbaugh; Songhu Wang (The Astronomical Journal, 2023)
Although close-orbiting, massive exoplanets—known as hot and warm Jupiters—are among the most observationally accessible known planets, their formation pathways are still not universally agreed upon. One method to constrain the possible dynamical histories of such planets is to measure the systems’ sky-projected spin–orbit angles using the Rossiter–McLaughlin effect. By demonstrating whether planets orbit around the stellar equator or on offset orbits, Rossiter–McLaughlin observations offer clues as to whether the planet had a quiescent or violent formation history. Such measurements are, however, only a reliable window into the history of the system if the planet in question orbits sufficiently far from its host star; otherwise, tidal interactions with the host star can erase evidence of past dynamical upheavals. We present a WIYN/NEID Rossiter–McLaughlin measurement of the tidally detached ( ${\boldsymbol{a}}/R_{* }={13.18}_{-0.37}^{+0.35}$ ) warm Jupiter WASP-106 b, which orbits a star along the Kraft break ( T _eff = 6002 ± 164 K). We find that WASP-106 b is consistent with a low spin–orbit angle ( $λ ={6}_{-16}^{+17}\,^° $ and $ψ ={26}_{-17}^{+12}\,^° $ ), suggesting a relatively quiescent formation history for the system. We conclude by comparing the stellar obliquities of hot and warm Jupiter systems, with the WASP-106 system included, to gain insight into the possible formation routes of these populations of exoplanets.